Surveying patients about their experience with a urinary catheter. Issue 1 (21st July 2015) - Darbyshire, Daniel; Rowbotham, Daniel; Grayson, Sarka; Taylor, Julia; Shackley, David
ABSTRACT: About 15–20% of hospital inpatients are catheterized, and it has been estimated that in an average sized hospital 10–15 patients will die each year from catheter‐related sepsis. Reducing catheterization rates or indwell times has been shown to reduce associated sepsis. This study examined patient experience of catheterization; the rationale for the study was to broaden understanding of catheter impact as part of a wider quality improvement agenda. Fifty patients completed a detailed catheter‐experience patient questionnaire. The patients were all inpatients from 17 wards across a range of specialties. Data were sought on demographics, catheter status, experience and their knowledge of and involvement in the catheter care. Fifty percent gender split. Median catheter time was 5 d (range 2 h to long term). Median age 72 years (range 22–92). Thirty‐four percent ( n = 17) of patients did not have the process and options discussed before catheterization. Eighteen percent did not know why they were catheterized. Patients experienced leaking (32%), 'pain' (26%), inconvenience (26%), embarrassment (24%), blocking (24%) with 8% finding their catheters 'restrictive'. Fourteen percent felt they could have coped without the catheter. Urinary catheters have a profound and often negative effect on the inpatient experience. This information can help support and empower colleagues to push for less urinary catheter use in the non‐urological inpatient population and start to better understand the patient experience.